Flood Assessment through Integrated-Mixed-Method in the Western Downstream Area of Citanduy River Basin, Pangandaran Regency - Syafitri, Dyah Rina; Arysandi, Safira Arum; Purboyo, Alvian Aji; Fitri, Amelia; Febriani, Yenni; Tjahyanityasa, Wanda Fitri; Sari, Nila Puspita; Mar'ath, Sitti Khafifatul; Safinatunnajah, Safinatunnajah; Satyaningrum, Aghnia Candra; Rahardjo, Noorhadi; Sudrajat, Sudrajat; Mardiatno, Djati; Rachmawati, Rini (Jurnal Pendidikan Geografi Gea, 2024)
Recurring and intensive flooding occurs in the western downstream area of the Citanduy River Basin (including Kalipucang, Padaherang, and Mangunjaya Districts, Pangandaran Regency) and causes massive losses. Land use Changes, fluctuating weather and climate conditions, as well as countermeasures that have not been maximized, have caused losses continuously. This study aims to describe the latest representation of flood vulnerability distribution in the study area using an integrated-mixed-method, includes: 1) AHP weighting based on expert interviews; 2) land use classification by the random forest algorithm; 3) Flood Hazard Map modeling using weighted overlay; and 4) hazard maps validation and historical flood analysis. The flood vulnerability model uses indicators: rainfall, elevation, slopes, distance from the river, and land use. Geographic Information System based on application (ArcGIS) and could (GEE) are the analytical tools in this study, supported by secondary data, such as 1) Sentinel 2A for land use models, 2) DEM for elevation and slope models, 3) buffer models for river distance and 4) CHIRPS for rainfall. The flood hazard with low and very-low levels is so minimal that it is less visible on the map. While the moderate level of flood hazard class counted as 12.6 Ha, mostly located in the eastern part of the study area (Padaherang and Kalipucang sub-districts).The high-level flood hazard class occupied about 2041.17 Ha, spread over built-up land use. The Very-high hazard class is 22652.11 Ha and mostly located in villages directly adjacent to the Citanduy River.